The Implementation of Child Violence Law which Caused the Fatal Death - Teguh Ariawan; Siti Rodhiyah Dwi Istinah; Denny Suwondo (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to determine and analyze the application of the law on child abuse that causes death with child perpetrators. The approach method used in this research is sociological juridical, emphasizing research that aims to obtain legal knowledge empirically by going directly to the object. Violence committed by minors resulting in the loss of a person's life must be enforced by law in accordance with its handling. The disappearance of life for the purpose of a crime, whether intentional or unintentional, cannot be justified by law. Law enforcement is a form of effort in creating justice for perpetrators and victims. The results of the study did not find anything that could eliminate criminal liability, either as a justification or excuse for forgiveness, so the child must be held accountable for his actions by being sentenced to imprisonment for 3 (three) years and 6 (six) months at the Child Special Guidance Institution (LPKA). Class I Kutoarjo.